Resilience promotes self-esteem in children and adolescents with hearing impairment: the mediating role of positive coping strategy - Qi, Ling; Zhang, Hongling; Nie, Rong; Du, Yukai (Frontiers in Psychology, 2024)
BackgroundThe level of self-esteem in adolescents appears to be contingent upon their satisfaction across various domains of life, exerting a notable influence on their mental wellbeing. The purposes of this study were to further validate the influence of resilience and positive coping strategy on their self-esteem and to explore the mediating effect of positive coping strategy in the relationship between resilience and self-esteem.MethodsA total of 657 children and adolescents with a hearing impairment from 14 deaf/special schools in Hubei province completed measures of self-esteem, resilience, and positive coping.Results(1) Self-esteem is positively correlated with resilience and positive coping, (2) resilience is a significant predictor of self-esteem, and (3) the association between resilience and self-esteem was partly mediated by a positive coping strategy.ConclusionThis study indicated the partly mediating effects of positive coping strategy on the association between resilience and self-esteem among Chinese children and adolescents with hearing impairment. These results also highlighted that intervention to promote resilience and coping strategies might be helpful to improve their self-esteem.